Rumble strips: a human factors perspective towards a sustainable road system - Shahren Ahmad Zaidi Adruce,; Donald Stephen, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Prior research substantiates the belief that human factors contribute to up to 90% of all traffic accidents. The failure to consider cognitive ergonomics in road safety initiatives will continue to cause traffic fatality, especially on straight roads. Since drivers and road safety practitioners cannot wholly avoid driver’s non-compliance, skill-based errors, and mistakes, road designs should aim to reduce the severity of repercussions resulting from human errors. For example, in the case of a momentary lapse of attention leading to lane departure, drivers should be able to correct their maneuvers. A human-centered traffic system approach of road design may reduce the severity of accidents caused by human error. An investigation of road crashes in Malaysia conducted by the Malaysian Institute of Road Safety Research revealed that 66% of road crashes in Malaysia are opposite-direction head-on crashes and run-off-road (roadway departure) crashes. Installing Lane Departure Warning System such as Centerline Rumble Strips (CLRS) and Shoulder Rumble Strips (SRS) can reduce these types of crashes and compensate human errors on the road. Rumble strips alert drivers that they are deviating from their lane by providing both tactile and auditory warnings. Although the effectiveness of rumble strips is well documented in prior researches, the practice of installing rumble strips is still scarce in Malaysia. This paper highlights how rumble strips can mitigate the consequences of the human errors, in the hope that the information can help road safety researchers, authorities, and practitioners move forward in the implementation of interventions towards sustainable road system.